2014
DOI: 10.1093/rheumatology/keu220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography as a useful modality for documenting sacroiliitis in radiographically negative inflammatory back pain: a comparative evaluation with MRI

Abstract: Three or more flow signals and a RI ≤0.605 can be applied as USG criteria for sacroiliitis. USG can be a cost-effective and non-inferior modality compared with MRI in documenting sacroiliitis in early SpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In fact, two radiographically negative but MRI positive cases for sacroiliitis showed vascularity on CDUS, suggesting the positive role in diagnosis of sacroiliitis in radiographically negative cases (Image 2, 3). This was in concordance to study done by Ghosh et al 30 However, in our study RI values between the range of 0.4 -0.7 were utilized, while they used RI values <0.605 as the cutoff for diagnosis of sacroiliitis. While the majority of patient (48%) showed at least 4 vascular foci, we set the lower limit at 2 foci as they formed 10% of the cases showing vascularity compared to those showing 5 foci (4%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, two radiographically negative but MRI positive cases for sacroiliitis showed vascularity on CDUS, suggesting the positive role in diagnosis of sacroiliitis in radiographically negative cases (Image 2, 3). This was in concordance to study done by Ghosh et al 30 However, in our study RI values between the range of 0.4 -0.7 were utilized, while they used RI values <0.605 as the cutoff for diagnosis of sacroiliitis. While the majority of patient (48%) showed at least 4 vascular foci, we set the lower limit at 2 foci as they formed 10% of the cases showing vascularity compared to those showing 5 foci (4%).…”
Section: Discussionsupporting
confidence: 90%
“…The procedure was performed for both sides. 30 The studies were performed by two radiologists having experience of 11 and 3 years, who were blinded to the clinical and radiography findings. In case of any contention, the findings were discussed to arrive at a mutual consent.…”
Section: Methodsmentioning
confidence: 99%
“…3. Can show some abnormal features of sacroiliac joints like effusion, bone surface erosion, and soft tissue swellings [9].…”
Section: Diagnostic Valuementioning
confidence: 99%
“…Finally, Ghosh et al conducted a study that combined CD and grey scale US of the sacroiliac joints in 29 patients with inflammatory LBP and normal X-ray and 32 controls, comparing the findings with MRI [33]. They found that the observation of three or more flow signals on CDUS and a RI below 0.605 correlated well with the MRI proven cases of sacroiliitis.…”
Section: Sij Dysfunctionmentioning
confidence: 99%